2014
DOI: 10.1615/intjmedmushr.v16.i3.80
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Nutritional and Medicinal Value of Fruit Bodies and Submerged Cultured Mycelia of Culinary-Medicinal Higher Basidiomycetes Mushrooms

Abstract: This research gives the results of a proximate analysis (moisture, ash, crude protein, fat, total carbohydrates, and total energy); a bioactive compounds analysis (γ-aminobutyric acid [GABA], ergothioneine, lovastatin, and cordycepin); fatty acid and amino acid analysis; and an analysis of macro- and microelement content of fruit bodies and mycelia of 15 higher Basidiomycetes medicinal mushroom strains belonging to 12 species. The results obtained demonstrate that almost all investigated mushrooms were found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
4
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 59 publications
4
102
4
5
Order By: Relevance
“…The nutritional value of some edible mushroom mycelia was comparable or even higher than those found in their fruiting body (Cohen et al, 2014). This clearly indicated that the mushroom mycelia have the potential to be harvested and utilized at an early stage instead of until the full fruiting body development.…”
Section: The Nutritional Compositions and Soluble Protein Contents Ofmentioning
confidence: 76%
“…The nutritional value of some edible mushroom mycelia was comparable or even higher than those found in their fruiting body (Cohen et al, 2014). This clearly indicated that the mushroom mycelia have the potential to be harvested and utilized at an early stage instead of until the full fruiting body development.…”
Section: The Nutritional Compositions and Soluble Protein Contents Ofmentioning
confidence: 76%
“…Following the total sugars variation during storage period, at oven dried mushrooms (Table 8), it can be seen that the largest content of sugars was recorded by untreated A. blazei with 14.70 g TS 100 g -1 DM at 6 months, 14.13 g DM), by Reis et al (2012), Pei et al (2014), Stojkovic et al (2014) and Jaworka et al (2015) for the total sugar content of A. bisporus mushroom (5.8-14.9 g 100 g -1 DM), respectively by Tsai et al (2008), Carneiro et al (2013), Cohen et al (2014) and Stojkovic et al (2014) for the total sugar content of A. blazei mushroom (13.4-31.3 g 100 g -1 DM).…”
Section: Fmmentioning
confidence: 87%
“…of the composition of 15 Basidiomycetes medicinal mushroom strains belonging to 12 species, including H. erinaceus fruiting body (FB) and mycelia biomass (MB), found that almost all investigated mushrooms are a good source of proteins and carbohydrates, the levels of which are 8.6−42.5 and 42.9− 83.6%, respectively, and that different species exhibited distinct free amino acid profiles. 2 The following information is limited to their reported findings with H. erinaceus. The analyses were performed on mushrooms dried at 50°C and then ground into a powder.…”
Section: ■ Nutrients Nutrition and Food Usementioning
confidence: 99%